Zirconium in the Nuclear Industry: Eleventh International Symposium 1996
DOI: 10.1520/stp16181s
|View full text |Cite
|
Sign up to set email alerts
|

A Unified Model to Describe the Anisotropic Viscoplastic Behavior of Zircaloy-4 Cladding Tubes

Abstract: This paper presents the constitutive equations of a unified viscoplastic model and its validation with experimental data. The mechanical tests were carried out in a temperature range of 20 to 400°C on both cold-worked stress-relieved and fully annealed Zircaloy-4 tubes. Although their geometry (14.3 by 1.2 mm) is different, the crystallographic texture was close to that expected in the cladding tubes. To characterize the anisotropy, mechanical tests were performed under both monotonic and cyclic uni- and bi-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 17 publications
2
2
0
Order By: Relevance
“…The Kearns factors [16] of the sheet used in the study were measured as f N =0.59, f L =0.05, and f T =0.31 in the normal, longitudinal/rolling, and transverse directions. These values are similar to those obtained in typical CWSR Zircaloy-4 nuclear fuel cladding tubes [17].…”
Section: Materials and Proceduressupporting
confidence: 88%
“…The Kearns factors [16] of the sheet used in the study were measured as f N =0.59, f L =0.05, and f T =0.31 in the normal, longitudinal/rolling, and transverse directions. These values are similar to those obtained in typical CWSR Zircaloy-4 nuclear fuel cladding tubes [17].…”
Section: Materials and Proceduressupporting
confidence: 88%
“…As described elsewhere [12], the sheet had strong crystallographic texture. Importantly, the Kearns factors [15] of this CWSR sheet (f N = 0.59, f R = 0.05, and f T = 0.31 in the normal, longitudinal/rolling, and transverse directions of the sheet, respectively) are similar to those reported for unirradiated CWSR Zircaloy-4 cladding tubes (0.58, 0.10, and 0.32, respectively) [16] if the hoop direction of the tube corresponds to the orientation transverse to the rolling direction of the sheet. Therefore, the texture of the Zircaloy-4 sheets used in this study is similar to the typical texture of Zircaloy-4 cladding tubes, i.e., the basal planes tend to align with their poles inclined approximately ± 30º away from the normal of the tube surface and oriented toward the transverse direction.…”
Section: Methodssupporting
confidence: 78%
“…This can be identi ed by the necking along tube z axis. In the previous studies, the parameter R values are found to be 1.3 tested in the axial direction 30) and 2.3 tested in the hoop direction 29) for unirradiated Zircaloy-4. On the contrary, it has been proved that the yield condition of irradiated nuclear fuel cladding is similar to those of isotropic materials, which illustrates that irradiation can reduce the anisotropic behavior of cladding tubes.…”
Section: Discussionmentioning
confidence: 92%